Correlation between antibiotic resistance and the presence of plasmid among enterobacteriaceae isolated from Rayu river Sarawak - Tang, Ping Sia (Universiti Malaysia Sarawak, UNIMAS, 2013)
Enterobacteriaaceae are natural habitat in the human and animal’s gastrointestinal tract that trigger disease by invasive action and production of toxin. To date, the occurrences of foodborne and waterborne illness due to Enterobacteriaceae infection has been increasing rapidly and thus raising the global awareness. Conditions become worse when most of the microorganisms become highly resistance to antibiotics. Emerging of antibiotic resistance among Enterobateriaceae was hazardous and complicating the treatment of disease associated with the enteric bacteria. Thus, present study was carried out to analyse the antibiotic resistance among Enterobacteriaceae, presence of plasmid and correlation between the antibiotic resistance and the plasmid presence in the isolates from Rayu River, Sarawak. The antibimicrobial susceptibility test shows that all of the isolates were susceptible to sulphamethoxazole trimethoprim (100%) and this was followed by norfloxacin and carbenicillin which both encountered 98.59%. About 44.48% of the isolates have MAR index higher than 0.2, implying that the areas have been highly contaminated with the application of antibiotics. The range of MAR index value obtained ranged from 0.75 to 0.5 was highly exceeds the standards of low risk contamination range. The molecular weights of plasmids detected ranged from 0.5 kb to 0.6 kb. It was rare for the occurrences of plasmid with molecular weight which was larger than 3 kb in Rayu River. Investigation showed that most of the plasmid posses more than one plasmid. Meanwhile, SPSS analysis shows that there were significant correlations between the antibiotic resistance with the presence of plasmid either in the form number or molecular weight of plasmid.